Chaves para ler as Memórias inventadas, de Manoel de Barros - Raquel R. Souza (Estudos de Literatura Brasileira Contemporânea)
Electing the book Memórias inventadas: a infância, by Brazilian poet Manoel de Barros, from the state of Goiás, the article intends to observe memory and as- sess the mechanisms through which it operates. From the basic assumption that memory is imagination, we search the theoretical support of the Phenomenology studies of Gaston Bachelard, relevantly in one of his last texts, which is dedicated to the examination of daydreaming and daydreaming about childhood. At the same time, we highlight the face of referential metapoetry as a focus of radiaton of those memories.